Cimentação adesiva: pastas de prova - Ansanello, Ana Carolina Calixto [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
The development and the popularization of operative techniques associated to adhesive dental materials valued aesthetic standards, transforming oral health conditions. Thus, aesthetic procedures in Dentistry add the purpose of returning form and function to the oral structures, harmonizing the smile and reinforcing the emotional comfort of the individual. The objective of this work was to review the literature on the use of adhesive cementation emphasizing the color selection of the cements, as well as to report the clinical case of a patient presenting the protocol of application of the slides used to predict the result to be reached in the procedures indirect restorers. In the planning of the case, the use of ceramic restorations in lithium disilicate in the teeth has been recommended 11, 12, 21, 22. Indirect techniques, despite their high cost and laboratory-dependent relationship, have several long-term advantages when compared to direct restorations in composite resin. Among them, superior aesthetics, greater resistance to wear, high resistance to abrasion, lower plate accumulation and chromatic stability. Following an implementation protocol carefully with an emphasis on selecting the color of the cement through the test folders, favors the achievement of a harmonious work, returning comfort and reaching the expectations of the patient

O desenvolvimento e a popularização de técnicas operatórias associadas a materiais odontológicos adesivos valorizou os padrões estéticos, transformando as condições de saúde bucal. Assim procedimentos estéticos na Odontologia, acrescem a finalidade de devolver forma e função às estruturas bucais, harmonizando o sorriso e reforçando o conforto emocional do indivíduo. O objetivo deste trabalho foi revisar a literatura acerca da utilização da cimentação adesiva enfatizando a seleção de cor dos cimentos, bem como relatar o caso clínico de uma paciente apresentando o protocolo de aplicação das pastas de prova utilizadas para prever o resultado a ser alcançado nos procedimentos restauradores indiretos. No planejamento do caso, foi preconizado a utilização de restaurações cerâmicas em dissilicato de lítio nos dentes 11,12, 21, 22. As técnicas indiretas, apesar do seu alto custo e da sua relação laboratório-dependente, possuem diversas vantagens em longo prazo quando comparadas as restaurações diretas em resina composta. Dentre elas, estética superior, maior resistência ao desgaste, alta resistência a abrasão, menor acúmulo de placa e estabilidade cromática. Seguir um protocolo de execução cuidadosamente com ênfase para a seleção da cor do cimento por meio das pastas de prova, favorece o alcance de um trabalho harmonioso, devolvendo conforto e alcançando as expectativas do paciente
Keywords: Porcelana dentária; Estética dentária; Cor; Dental ceramics